DIGITALIZATION PROCESS IN LATVIA BANKING SECTOR 2012-2020 - Gutorova, Irīna; Borisova, Elva Kristiāna; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
This article is related with digitalization process in Latvia banking sector 2012-2020. The main guideline of the article is assumption that bank clients prefer to use internet neither to come directly into a bank for consultations. In computer age, everything can be done using smartphones and other gadgets, therefore it is easier to find answers to questions using assisting software. The European Union has passed out new directive, that appoints to give a possibility for citizens to complete all their payments in faster, simpler and more convenient way, as well as to promote the development of innovations, at the same time improving the safety of payments and standardize the payment systems all around the Europe. This article points out that mobile applications take a big part in every day of bank clients’ lives, therefore there is an proposal to create a consolidated internet bank and the mobile “wallet”, which would allow to access bank accounts, which are in different banks, that is fast and effectively solution based on software usage. As a result, there is digitalization process in banking sector not only in Latvia but in Europe as well.